Advanced liver disease in Russian children and adolescents with chronic hepatitis C. Issue 7 (7th April 2019) - Turkova, Anna; Volynets, Galina V.; Crichton, Siobhan; Skvortsova, Tamara A.; Panfilova, Victoria N.; Rogozina, Natalia V.; Khavkin, Anatoly I.; Tumanova, Elena L.; Indolfi, Giuseppe; Thorne, Claire
Summary: Russia has one of the highest prevalences of paediatric chronic hepatitis C infection (CHC). Our aim was to provide a detailed characterization of children and adolescents with CHC including treatment outcomes. Thus, an observational study of children with CHC aged <18 years was conducted in three hepatology centres from November 2014 to May 2017. Of 301 children (52% male), 196 (65%) acquired HCV vertically, 70 (23%) had a history of blood transfusion or invasive procedures, 1 injecting drug use and 34 (11%) had no known risk factors. Median age at HCV diagnosis was 3.1 [interquartile range, IQR 1.1, 8.2] and 10.8 [7.4, 14.7] at last follow‐up. The most common genotype was 1b (51%), followed by 3 (37%). Over a quarter of patients (84, 28%) had raised liver transaminases. Of 92 with liver biopsy, 38 (41%) had bridging fibrosis (median age 10.4 [7.1, 14.1]). Of 223 evaluated by transient elastography, 67 (30%) had liver stiffness ≥5.0 kPa. For each year, increase in age mean stiffness increased by 0.09 kPa (95% CI 0.05, 0.13, P  < 0.001). There was significant correlation between liver stiffness and biopsy results (Tau‐b = 0.29, P  = 0.042). Of 205 treated with IFN‐based regimens, 100 (49%) had SVR24. Most children (191, 93%) experienced adverse reactions, leading to treatment discontinuation in 6 (3%). In conclusion, a third of children acquired HCV via nonvertical routes and a substantial proportion of those with liver biopsy had advanced liver disease. Only half of children achieved SVR24 with IFN‐based regimens highlighting the need for more effective and better‐tolerated treatments with direct‐acting antivirals. Further studies are warranted in Russia on causes and prevention of nonvertical transmission of HCV in children.